Switching cycles in Steiner triple systems - Grannell M.J.,; Griggs T.S.,; Murphy J.P., (Utilitas Mathematica, 1999)
We investigate equivalence classes under the operation of n-cycle switching on isomorphism classes of STS (v)s for v ∈ {7, 9, 13, 15} and n ∈ {4,6,8, 10, 12}. We also investigate equivalence classes under the operation of n-cycle switching on realizations of STS(v)s on a fixed base set V for v ∈ {7, 9, 13} and n ∈ {4, 6, 10}, and for (v, n) = (15, 12).